1996
DOI: 10.1085/jgp.107.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Ion permeation through light-activated channels in rhabdomeric photoreceptors. Role of divalent cations.

Abstract: A B S T RA C T The receptor potential of rhabdomeric photoreceptors is mediated primarily by a Na influx, but other ions must also permeate through light-dependent channels to account for some properties of the photoresponse. We examined ion conduction in macroscopic and single-channel light-induced currents of Lima and Pecten photoreceptors. In the absence of Na, a fivefold change in extracellular K shifted the reversal voltage of the photocurrent (V~v) by ~ 27 mV. Because the dependency of Vre v on [K] o was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
(63 reference statements)
1
15
0
Order By: Relevance
“…Detailed analysis of selective permeation would require examining the ionic dependency of the reversal potential, but the strong inward rectification of the photocurrent did not allow such measurements. Nonetheless, the differential role for Na and Ca is reminiscent of light-dependent ion channels in various invertebrate rhabdomeric photoreceptors (35,36). Membrane current fluctuations elicited by dim light were rapid and only a few picoamperes in amplitude; on the assumption that these waves represent quantal responses, the transduction gain would appear to be only severalfold greater than in mouse ipRGCs (37); the much larger overall light sensitivity of Amphioxus (2-3 orders of magnitude) may, thus, be due chiefly to higher expression levels of melanopsin.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of selective permeation would require examining the ionic dependency of the reversal potential, but the strong inward rectification of the photocurrent did not allow such measurements. Nonetheless, the differential role for Na and Ca is reminiscent of light-dependent ion channels in various invertebrate rhabdomeric photoreceptors (35,36). Membrane current fluctuations elicited by dim light were rapid and only a few picoamperes in amplitude; on the assumption that these waves represent quantal responses, the transduction gain would appear to be only severalfold greater than in mouse ipRGCs (37); the much larger overall light sensitivity of Amphioxus (2-3 orders of magnitude) may, thus, be due chiefly to higher expression levels of melanopsin.…”
Section: Discussionmentioning
confidence: 99%
“…E xtracellular chemical stimulation was accomplished by a puffer pipette (tip outer diameter of 3-4 m) positioned ϳ30 -50 m from the target cell. Application of pressurized nitrogen (1-3 psi) to the pipette via a solenoidoperated valve permitted local solution exchange in Ͻ400 msec (Gomez and Nasi, 1996). Patch electrodes were fabricated with thin-wall borosilicate capillary tubing (7052, Garner Glass, C laremont, CA), fire-polished, and filled with an "intracellular" solution containing (in mM) 100 KC l, 200 K-aspartate or K-glutamate, 5 Na 2 ATP, 12 NaC l, 6 MgC l 2 , 10 H EPES, 1 EGTA, 0.2 GTP and 300 sucrose, pH 7.3.…”
Section: Methodsmentioning
confidence: 99%
“…To apply test substances extracellularly, we relied on a local perf usion technique consisting of a puffer micropipette positioned in the vicinity of the cell that could pressure eject a stream of test solution on activation of a solenoidoperated valve. Previous measurements obtained with a fluorescent dye included in the puffer pipette demonstrated that ϳ95% of solution exchange is attained within 200 -400 msec, and that the ejection plume completely engulfs the region occupied by the target cell, as visualized with an image-intensified CCD camera (Gomez and Nasi, 1996a). Alternatively, in some experiments, test compounds were administered intracellularly by dialysis via the patch electrode.…”
mentioning
confidence: 99%